Identification and Infrared Spectroscopic Study of Lapachol, β-Lapachone and Hydroxy-hydrolapachol - Gomes, Miquéias Ferreira; Araújo, Ginandrya Rodrigues; Silva, Ziom Drak Souza; de Sousa, Raquel Maria Ferreira; Dias, Herbert Júnior (Archives of Pharmacy and Pharmaceutical Sciences, 2023)
Metabolites of Brazilian Cerrado species are considered an immense font of biologically active compounds The diversity of organic compounds generated by the secondary metabolism of various Cerrado plants draws attention especially because many of these compounds have the capacity to be structurally modified and, consequently, produce other very interesting derivatives for pharmacological purposes. Despite this, little is described in the literature about fast, easy, and accessible identification methods for any laboratory, such as infrared spectroscopy. In this sense, this work demonstrates the synthesis and elucidation through spectroscopic techniques of lapachol and its synthetic derivatives. Through quick and simple extractions or reactions, lapachol, β-lapachone, and hydroxy-hydrolapachol were obtained with adequate yields. From this, the main FTIR absorptions of the mentioned naphthoquinones are described, which facilitates the identification of these metabolites with high biological potential. The present work contributes could become a simpler source of data for extraction, synthesis, and spectroscopic characterization by FTIR of the compounds.